PATOGENICIDADE DE ð˜‰ð˜¦ð˜¢ð˜¶ð˜·ð˜¦ð˜³ð˜ªð˜¢ ð˜£ð˜¢ð˜´ð˜´ð˜ªð˜¢ð˜¯ð˜¢ (BALS.) E ð˜”ð˜¦ð˜µð˜¢ð˜³ð˜©ð˜ªð˜»ð˜ªð˜¶ð˜® ð˜¢ð˜¯ð˜ªð˜´ð˜°ð˜±ð˜ð˜ªð˜¢ð˜¦ (METSCH.) SOROK SOBRE ð˜Šð˜¢ð˜´ð˜µð˜¯ð˜ªð˜¢ ð˜ªð˜¤ð˜¢ð˜³ð˜¶ð˜´ (CRAMER, 1775) - Silva, Ranyse B. Q. da; Veiga, AntÃ´nio F. de Souza LeÃ£o (REVISTA DE AGRICULTURA, 2020)
PATOGENICIDADE DE ð˜‰ð˜¦ð˜¢ð˜¶ð˜·ð˜¦ð˜³ð˜ªð˜¢ ð˜£ð˜¢ð˜´ð˜´ð˜ªð˜¢ð˜¯ð˜¢ (BALS.) E ð˜”ð˜¦ð˜µð˜¢ð˜³ð˜©ð˜ªð˜»ð˜ªð˜¶ð˜® ð˜¢ð˜¯ð˜ªð˜´ð˜°ð˜±ð˜ð˜ªð˜¢ð˜¦ (METSCH.) SOROK SOBRE ð˜Šð˜¢ð˜´ð˜µð˜¯ð˜ªð˜¢ ð˜ªð˜¤ð˜¢ð˜³ð˜¶ð˜´ (CRAMER, 1775)